Stokes drift and particle trajectories induced by surface waves atop a shear flow - Li, Yan; Zheng, Zibo; Kalisch, Henrik (Frontiers in Marine Science, 2024)
Surface waves and currents are crucial to the mass transfer in the air-sea interaction as they can drive a variety of dynamical processes. How mass can be transported by surface waves and current coupling is addressed through a study of their induced motions of fluid parcels. To this end, a weakly nonlinear wavetrain is imposed on the background flow whose direction and magnitude are permitted to vary with water depth and second-order features of this configuration are investigated. A leading-order approximation to the Stokes drift is derived, correct to the